2010
DOI: 10.1002/erv.969
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric evaluation of a Brazilian version of the impact of weight on quality of life (IWQOL‐Lite) instrument

Abstract: The IWQOL-Lite is the first specific instrument validated in Brazil for assessing quality of life in obesity. The results reveal that IWQOL-Lite is an instrument with good psychometric properties. Nevertheless, in some cases results were dissimilar to those reported in earlier studies using the original American English.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
(34 reference statements)
2
10
1
Order By: Relevance
“…Similarly, these Spanish patients scored slightly higher on physical function, self-esteem, and work and had higher total transformed scores, than did the severely obese patients studied in the German validation [13] of the IWQOL-Lite (A. Mueller, personal communication). By contrast, the present study found lower quality of life in the sexual life and public distress domains compared with the German data, as well as in comparison to clinical and community samples from Brazil and Portugal [12,18]. These differences are likely due to the different nature of the samples used in these studies, since subjects seeking surgery to correct their weight problem would be expected to be more negatively affected by obesity than would other obese patients [3,35].…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…Similarly, these Spanish patients scored slightly higher on physical function, self-esteem, and work and had higher total transformed scores, than did the severely obese patients studied in the German validation [13] of the IWQOL-Lite (A. Mueller, personal communication). By contrast, the present study found lower quality of life in the sexual life and public distress domains compared with the German data, as well as in comparison to clinical and community samples from Brazil and Portugal [12,18]. These differences are likely due to the different nature of the samples used in these studies, since subjects seeking surgery to correct their weight problem would be expected to be more negatively affected by obesity than would other obese patients [3,35].…”
Section: Discussioncontrasting
confidence: 97%
“…Scores for each subscale and a total score are obtained. Previous studies have reported adequate corrected item-total correlations and internal consistency coefficients in bariatric surgery patients, as well as in a variety of clinical and community samples [12,13,[15][16][17][18]25]. Factor analysis has also supported the construct validity of the questionnaire [15][16][17][18].…”
Section: Quality Of Lifementioning
confidence: 92%
See 3 more Smart Citations